Efisiensi Probiotik Mina Pro dan Suplementasi Vitamin C Dalam Pakan Komersil Untuk Budidaya Intensif Ikan Lele (Clarias gariepinus) Fase Pendederan IV - Satria, Muhammad Akbar; Rostika, Rita; Grandiosa, Roffi; Zidni, Irfan (Jurusan Ilmu Kelautan dan Perikanan Politeknik Negeri Pontianak, 2024)
Catfish is a popular and widely consumed fishery commodity in Indonesia, offering promising prospects in terms of demand and selling price. The purpose of this study was to determine how efficient the use of Mina Pro probiotics and vitamin C supplementation in feed in intensive cultivation of catfish. This research was conducted at the Aquaculture Laboratory Building 4 Faculty of Fisheries and Marine Science, Padjadjaran University, this research began in May to July 2024. The experimental design used the complete randomized design (CRD) method with 4 treatments (A: no added probiotics Mina Pro and vitamin C); (B: 6 ml/kg probiotics and 3 grams/kg vitamin C feed); (C: 8 ml/kg probiotics and 3 grams/kg vitamin C feed); (D: 10 ml/kg probiotics and 3 grams/kg vitamin C feed) and replicated four times. Parameters observed in this study were fish growth rate (length and weight), specific growth rate (SGR), daily growth rate, feed conversion ratio (FCR),survival rate, and water quality. Data analysis using analysis of variance (ANOVA) using the F test with a confidence level of 95%, if there is a significant difference between the treatments carried out then a further test is carried out, namely the Duncan test with a real test level of 5%. The results showed that treatment B showed the best results which had an average absolute length gain of 5.93 cm, then an average absolute weight gain of 15.54 grams, for specific growth rate (SGR) with a percentage of 3.01%, daily growth rate of 0.23 gr/day, then feed conversion ratio (FCR) of 0.127 ± 0.007, and survival rate with a percentage of 82%.